1987
DOI: 10.1063/1.453388
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of gas-phase reactions of polyatomic carbon ions C+n(n=1–6) and CnH+(n=2–5) with carbon monoxide

Abstract: The selected-ion flow tube (SIFT) technique has been employed in the study of reactions of carbon monoxide with the polyatomic carbon cations C+n(n=1−6) and CnH+(n=2–5) at 296±2 K in helium buffer gas at ∼0.34 Torr and 1.1×1016 atoms cm−3. The polyatomic carbon cations were generated by electron impact on a suitable parent molecule. Carbon monoxide was observed to add rapidly to C+n(n=2–6) twice in succession to form polyatomic carbon monoxide and dioxide cations, and once to CnH+ to form polyatomic carbon mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Charged analogues of C 5 H have also received comparatively little attention. Bohme and co-workers have reported a number of ion−molecule reactions of the C 5 H cation . Formed from electron impact ionization of 1,4-pentadiyne by a mechanism that is not clear, the C 5 H + ion observed is assumed to adopt a linear structure (since low-level calculations have suggested this cation to be stable with a linear geometry 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charged analogues of C 5 H have also received comparatively little attention. Bohme and co-workers have reported a number of ion−molecule reactions of the C 5 H cation . Formed from electron impact ionization of 1,4-pentadiyne by a mechanism that is not clear, the C 5 H + ion observed is assumed to adopt a linear structure (since low-level calculations have suggested this cation to be stable with a linear geometry 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bohme and co-workers have reported a number of ion-molecule reactions of the C 5 H cation. 29 Formed from electron impact ionization of 1,4-pentadiyne by a mechanism that is not clear, the C 5 H + ion observed is assumed to adopt a linear structure (since low-level calculations have suggested this cation to be stable with a linear geometry 14 ). Of more interest, however, is related work by the same group that shows that reaction between cationic carbon and neutral diacetylene leads to rapid formation of C 5 H + .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that small C,+ (n < 10) cluster ions are more reactive than larger ones [2,3] and also undergo different * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since Douglas 1 proposed carbon chains as possible carriers of the diffuse interstellar bands (DIBs), the linear carbon clusters, including pure carbon chains and their heteroatom‐containing derivatives, have attracted a considerable attention, both experimentally and theoretically 2–9. Among these clusters, the hydrogen‐doped carbon clusters as the most important species have been investigated extensively 10–37.…”
Section: Introductionmentioning
confidence: 99%
“…In 1982, Wilson and Green 34 predicted the bond lengths and rotational constants of C 2 H + and C 4 H + by theoretical calculations, although their ground states are still unclear. The selected‐ion flow tube (SIFT) technique has been used to explore gas‐phase reactions of carbon monoxide with the polyatomic carbon cations C n H + ( n = 2–5) 35. The vertical electronic spectrum of linear C 5 H + has been predicted by ab initio multireference configuration interaction (MRD‐CI) calculations 36.…”
Section: Introductionmentioning
confidence: 99%